'By indirections find directions out': Shakespeare, his Restoration adapters, and early modern myths of nature. Issue 90 (July 2016) - Hattaway, Michael
The article will, by analysing appropriations by Nahum Tate and other Restoration writers of particular Shakespearean speeches, erect hypotheses concerning Shakespeare's distinctive ways of writing heuristically. Shakespeare 'thought with' rather than 'thought about' words, concepts, images and tales and negotiated in a distinctive manner with myths of nature.